A Comparative Analysis of Pinned and Fixed Base Supports in Building Structural Modeling - heri kasyanto; Irgi Fazri Fahrezi; Sania Hanifa (Potensi: Jurnal Sipil Politeknik, 2026)
In structural modeling, the superstructure and substructure are often analyzed separately. The choice of support for the superstructure should reflect the substructure’s behavior whether fixed, pinned, a combination, or spring based. In this study, two similar model with different support, that is pinned and fixed supports will be analyzed and the results subsequently compared to evaluate structural performance. An office building in Bandung, West Java, with a reinforced concrete frame was selected as the study object, and building irregularities were disregarded in the analysis. The natural periods, inter-story drift, as well as the demand capacity ratio resulted from the models were evaluated through this study. The results of this study show that pinned supports building model yields an average value of story drift that is 18.66% greater in the X direction and 19.33% greater in the Y direction compared to fixed supports building model. The demand capacity ratio of the pinned support building model was also 5.29% greater than that of fixed support, indicates that the required strength (internal force) of structural elements in models with pinned support is greater than fixed support.